Early IL-1 Signaling Promotes iBALT Induction after Influenza Virus Infection - Neyt, Katrijn; GeurtsvanKessel, Corine H.; Deswarte, Kim; Hammad, Hamida; Lambrecht, Bart N. (Frontiers in Immunology, 2016)
Inducible Bronchus Associated Lymphoid Tissue (iBALT) is a long lasting tertiary lymphoid tissue that can be induced following influenza A virus (IAV) infection. Previous studies have shown that iBALT structures containing germinal center (GC) B cells protect against repeated infection by contributing locally to the cellular and humoral immune response. If we are to exploit this in vaccination strategies, we need a better understanding on how iBALT structures are induced. One hypothesis is that the strength of the initial innate response dictates induction of iBALT. In the present study, we investigated the role of IL-1 and IL-1R signalling on iBALT formation. Mice lacking the IL-1R, had a delayed viral clearance and thus a prolonged exposure to viral replication, leading to increased disease severity compared to wild type mice. Contradictorily, iBALT formation following clearance of the virus was heavily compromised in Il1r1-/- mice. Quantification of gene induction after IAV infection demonstrated induction of IL-1α and to a much lesser extent of IL-1β. Administration of recombinant IL-1α to the lungs of wild type mice early and late after IAV infection, led to more pronounced iBALT formation and an increased amount of GC B cells in the lungs. Bone marrow chimeric mice identified the stromal compartment as the crucial IL-1 responsive cell for iBALT induction. Mechanistically, Q-PCR analysis of lung homogenates revealed a strongly diminished production of CXCL13, a B cell attracting chemokine, in Il1r-/- mice during the early innate phase of IAV infection. These experiments demonstrate that appropriate innate IL 1α - IL 1R signalling is necessary for IAV clearance and at the same time instructs the formation of organized tertiary lymphoid tissues through induction of CXCL13 early after infection. These findings are discussed in the light of recent insights on the pathogenesis of TLO formation in the lung in various diseases where the IL-1 axis is hyperactive such as rheumatoid arthritis and COPD.